Colonial Oppression's Alteration of Identity - Pedersen, Ellen-Marie Sørhus (2016)
Famines may be a threat to the victims' own identity, therefore it is essential to establish a collective memory. In Ireland the potato famine had devastating effects on the Irish identity, much like the Sami situation in Norway, where they suffered under religious oppression resulting in famine. These stories center around the desperation victims are experiencing, which alters their identity, leading to violent behavior. When their government abandons them, they are forced to act on their own, which in turn causes the government to fight against this newfound independence. As the peoples' identity changes, their rebellion against their own government affects generations to come and their culture. Tom Murphy's play Famine and Nils Gaup's Norwegian film The Kautokeino Rebellion attempts to illustrate this process and how, when faced with horrible tragedy under oppressive colonization, identities are greatly changed and worldviews challenged. Ellen-Marie Sørhus Pedersen, originally from Holmestrand, Norway, is an English Literature major and a History minor. This project was presented at the 2016 Celebration of Student Scholarship.